ULTRASOUND DIAGNOSIS OF TEMPOROMANDIBULAR JOINT IN PATIENTS WITH CRANIOMANDIBULAR DYSFUNCTIONS - Mariana Dimova-Gabrovska; Desislava Dimitrova; Bozhidar Yordanov; Nikolay Apostolov; Todor Peev (Peytchinski Publishing, 2019)
In patients suffering from craniomandibular dysfunctions, early diagnosis of the problems and recognition of the signs and symptoms of functional pathology is of particular importance for duly managing and restoring these abnormalities to the physiological norm, thus ensuring the functional health of the masticatory system. Because of the specific location and nature of these abnormalities, the diagnosis is frequently difficult, and additional diagnostic imaging methods are required. The aim of this review is to analyze and present the latest scientific evidence on the use of ultrasound diagnosis of the temporomandibular joint in patients with craniomandibular dysfunctions. Material and methods: An electronic search by keywords was performed in PubMed, Google and Lilac databases from September 2018 to March 2019. The collected data were subject to critical analysis. Results: The basic principles of application, various methods and techniques, advantages and disadvantages and the diagnostic accuracy of ultrasonography in the evaluation of joint-jaw relationships were examined. The relevant parameters for determining the norm and the various pathologies were presented. Conclusion: Ultrasonography is a non-invasive, reliable, effective and easy-to-use method for diagnostic imaging of temporomandibular disorders in the dental office.